Patient outcomes from time of listing for lung transplantation in the UK: are there disease-specific differences?. Issue 1 (3rd October 2018) - Kourliouros, Antonios; Hogg, Rachel; Mehew, Jenny; Al-Aloul, Mohamed; Carby, Martin; Lordan, James Laurence; Thompson, Richard Damian; Tsui, Steven; Parmar, Jasvir
Abstract : Background: The demand for lung transplantation vastly exceeds the availability of donor organs. This translates into long waiting times and high waiting list mortality. We set out to examine factors influencing patient outcomes from the time of listing for lung transplantation in the UK, examining for differences by patient characteristics, lung disease category and transplant centre. Methods: Data were obtained from the UK Transplant Registry held by NHS Blood and Transplant for adult lung-only registrations between 1January 2004 and 31 March 2014. Pretransplant and post-transplant outcomes were evaluated against lung disease category, blood group and height. Results: Of the 2213 patient registrations, COPD comprised 28.4%, pulmonary fibrosis (PF) 26.2%, cystic fibrosis (CF) 25.4% and other lung pathologies 20.1%. The chance of transplantation after listing differed by the combined effect of disease category and centre (p<0.001). At 3 years postregistration, 78% of patients with COPD were transplanted followed by 61% of patients with CF, 59% of other lung pathology patients and 48% of patients with PF, who also had the highest waiting list mortality (37%). The chance of transplantation also differed by height with taller patients having a greater chance of transplant (HR: 1.03, 95% CI: 1.02 to 1.04, p<0.001). Patients with blood group O had the highest waiting mortality at 3 years postregistration compared with all other blood groups (27% vs 20%, p<0.001). Conclusions: The way donor lungs were allocated in the UK resulted in discrepancies between the risk profile and probability of lung transplantation. A new donor lung allocation scheme was introduced in 2017 to try to address these shortcomings.